Colton 911: secret defender - Ferrarella, Marie (Colton 911: Chicago, 2021)
"When he meets skittish Felicia Wagner, ex-boxer Aaron Colton immediately senses she's hiding something. He makes it his mission to figure out what she's hiding...and soon discovers Felicia is keeping a dangerous secret. A threat from her past looms large over her present, and Aaron offers to keep her safe. Even if that means resisting their mutual attraction. Even if that means risking it all..."--Back cover.